Management of Cushing syndrome: the tough questions - Yuen, Kevin C.J. (Henry Stewart Talks, 2024)
Cushing syndrome (CS), Cyclical CS, late-night salivary cortisol, Challenges associated with screening tests for CS, Pituitary surgery, Current treatment options all have limitations